Does Topical Capsaicin Affect the Central Nervous System in Neuropathic Pain? A Narrative Review - Kareem Alalami; Jenna Goff; Hannah Grimson; Oliver Martin; Eloise McDonald; Thonima Mirza; Dhruvi Mistry; Adanma Ofodile; Sara Raja; Tooba Shaker; Danah Sleibi; Patrice Forget (MDPI AG, 2024)
Research has been conducted investigating the neuronal pathways responsible for the generation of chronic neuropathic pain, including the components of it in conditions such as chronic post-surgical pain, phantom limb pain, and cluster headaches. Forming part of the management of such conditions, capsaicin as a molecule has proven effective. This review has investigated the central nervous system modifications exhibited in such conditions and the pharmacological mechanisms of capsaicin relevant to this. The current paradigm for explaining topical capsaicin-induced analgesia is that TRPV1-mediated calcium ion influx induces calpain, in turn causing axonal ablation and functional defunctionalisation in the PNS (Peripheral Nervous System). Demonstrated through the analysis of existing data, this review demonstrates the changes seen in the CNS (Central Nervous System) in chronic neuropathic pain, as well as some of the evidence for capsaicin modulation on the CNS. Further supporting this, the specific molecular mechanisms of capsaicin-induced analgesia will also be explored, including the action of TRPV1, as well as discussing the further need for clinical research into this area of uncertainty due to the limited specific data with suitable parameters. Further research this review identified as potentially useful in this field included fMRI (functional Magnetic Resonance Imaging) studies, though more specific observational studies of patients who have already been administered capsaicin as a current treatment may prove helpful in studying the modification of the CNS in the long term.